Late‐onset hypogonadism: metabolic impact. (25th September 2019) - Grossmann, M.; Ng Tang Fui, M.; Cheung, A. S.
Abstract: Background: Obesity and dysglycemia (comprising insulin resistance, the metabolic syndrome and type 2 diabetes), that is diabesity, are associated with reduced circulating testosterone and, in some men, clinical features consistent with androgen deficiency. Objective: To review the metabolic impact of late‐onset hypogonadism. Methods: Comprehensive literature search with emphasis on recent publications. Results: Obesity is one of the strongest modifiable risk factors for late‐onset hypogonadism, and coexisting diabetes leads to further hypothalamic‐pituitary‐testicular axis suppression. The hypothalamic‐pituitary‐testicular axis suppression is functional and hence potentially reversible, and occurs predominantly at the level of the hypothalamus. While definitive mechanistic data are lacking, the evidence suggests that hypothalamic‐pituitary‐testicular axis suppression is mediated by dysregulation of pro‐inflammatory cytokines leading to hypothalamic inflammation. Dysregulation of central leptin and insulin signaling may also contribute. In contrast, recent data challenge the paradigm that estradiol excess is a major contributor to hypothalamic‐pituitary‐testicular axis suppression. Instead, relative estradiol signaling deficiency may contribute to metabolic dysregulation in men with diabesity. While weight loss and optimization of comorbidities can reverse functional hypothalamic‐pituitary‐testicular axis suppression, testosterone treatment leads to metabolically favorable changes in body composition and to improvements in insulin resistance. Discussion: The relationship between diabesity and late‐onset hypogonadism is bidirectional. Preliminary evidence suggests that, in carefully selected men, lifestyle measures and testosterone treatment may have additive effects. Conclusions: While recent research has provided new insights into mechanistic and clinical aspects of diabesity‐associated late‐onset hypogonadism, more evidence from well‐designed large trials is needed to guide the optimal clinical approach to such men.